Library automation : What is expected of? - Rao, I.K. Ravichandra (DESIDOC Journal of Library & Information Technology, 2002)
Although a number of developments are taking place in the field of information technology and the hardware is readily available at affordable prices, libraries in India have not yet gone for automation in a big way. It is partly due to lack of trained manpower and non availability of suitable software. This paper attempts to discuss the areas of computerisation in libraries, the objectives and functions of computerised acquisition, serials control, circulation, and cataloguing. http://dx.doi.org/10.14429/dbit.15.2.3181